History of Low Birth Weight and Exclusive Breastfeeding on the Incidence of Acute Respiratory Infection in Children Under Five Years - Asthiningsih, Ni Wayan Wiwin; Milkhatun, Milkhatun; Rizal, Alfi Ari Fakhrur (University of Muhammadiyah Semarang, 2022)
Acute Respiratory Infections (ARI) are one of the main causes of infectious disease morbidity and mortality worldwide. Acute Respiratory Infection (ARI) is a health problem that often occurs in children, and the group most at risk is children under five years. This study aimed to determine the relationship between nutritional status and exclusive breastfeeding on the incidence of ARI in the working area of the Loa Bakung Public Health Center, Samarinda. This type of research is quantitative research using a cross-sectional approach. The samples in this study were parents of children under five who visited the Posyandu in the working area of the Loa Bakung Public Health Center, Samarinda. The sampling technique used was purposive sampling with a total sample of 181 respondents. The analytical test used in this research is chi-square. The chi-square test results on the history of LBW obtained a p-value = 0.373 and exclusive breastfeeding with a p-value = 0.440. This shows no relationship between a history of LBW and exclusive breastfeeding on the incidence of ARI at the Loa Bakung Public Health Center, Samarinda. The incidence of ARI in children under five years at the Loa Bakung Public Health Center, Samarinda, is not influenced by a history of LBW and exclusive breastfeeding. Still, other factors could have influenced the incident that was not carried out in this study. The role of parents is very important in maintaining the health of their children under five years to prevent the occurrence of ARI in their children under five years.